Coronary angioplasty in unstable angina and stable angina: a comparison of success and complications. Issue 5 (November 1988) - Perry, R A; Seth, A; Hunt, A; Shiu, M F
Abstract : One hundred and five patients with unstable angina and 175 with chronic stable angina were treated by primary percutaneous transluminal coronary angioplasty. Patients with unstable angina had had symptoms for a shorter time and were more likely to have angiographically complex lesions and lesions less than 10 mm in length than patients with chronic stable angina. Other baseline variables were not significantly different in the two groups. The overall primary success rate was similar in both groups (87% v 86%). Nine of the 14 unsuccessful procedures in those with unstable angina and nine of the 24 unsuccessful procedures in those with stable angina were the result of acute occlusion. These results led to a 9% frequency of procedure related myocardial infarction in patients with unstable angina and a 5% rate in those with stable angina (NS). The procedure related infarct rate tended to be higher in patients with unstable angina who had coronary angioplasty soon after an episode of unstable angina (mean 10 days) than in those in whom it was delayed (mean 35 days) (12% v 3%) (NS). In patients with unstable angina who had had a previous myocardial infarction procedure related infarction was significantly more common (18%) than in patients with no previous myocardial infarction (3%). The difference between those with and without previous infarction was also significant in patients with stable angina (10% v 3%).